2020
DOI: 10.1503/cmaj.191283
|View full text |Cite
|
Sign up to set email alerts
|

Use of sodium–glucose cotransporter-2 inhibitors and risk of acute kidney injury in older adults with diabetes: a population-based cohort study

Abstract: S odium-glucose cotransporter-2 (SGLT2) inhibitors became available to treat type 2 diabetes in Canada in 2014. There are 4 SGLT2 inhibitors available: canagliflozin, dapagliflozin, empagliflozin and ertugliflozin. 1 In addition to effectively lowering blood glucose levels, they also prevent adverse cardiovascular events. 2-5

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
62
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(64 citation statements)
references
References 56 publications
(63 reference statements)
2
62
0
Order By: Relevance
“…In individual CVOTs, AKI risk was either neutral or reduced with SGLT2 inhibitors, and in meta-analyses involving cardiorenal outcome studies, AKI risk was reduced by approximately 25% [ 7 10 , 17 , 18 ]. Similarly, in propensity-matched score analyses with electronic medical record data, AKI risk was lower with SGLT2 inhibitors than with other glucose-lowering therapies [ 29 ]. Consistent with this previous literature, our analysis found no indication of an increase in AKI risk with ertugliflozin.…”
Section: Discussionmentioning
confidence: 99%
“…In individual CVOTs, AKI risk was either neutral or reduced with SGLT2 inhibitors, and in meta-analyses involving cardiorenal outcome studies, AKI risk was reduced by approximately 25% [ 7 10 , 17 , 18 ]. Similarly, in propensity-matched score analyses with electronic medical record data, AKI risk was lower with SGLT2 inhibitors than with other glucose-lowering therapies [ 29 ]. Consistent with this previous literature, our analysis found no indication of an increase in AKI risk with ertugliflozin.…”
Section: Discussionmentioning
confidence: 99%
“…Adverse event (AE) post-marketing reporting on AKI led the US Food and Drug Administration to issue warnings for SGLT2i to be used with caution in patients at risk of AKI. 9 However, data from clinical trials, 1,3,4,10 and large observational cohorts, [11][12][13][14] reported reduced AKI risk with SGLT2i.…”
Section: Introductionmentioning
confidence: 99%
“…Rampersad et al have therefore reported a robust clear clinical message about the kidney safety of SGLT2-inhibitor use in the real world, regardless of the definition of AKI, that is consistent with observations from clinical trials and other recent large retrospective propensity-matched cohort studies. 14 The consistency of this analysis is a major strength and should provide reassurance to both health care providers and patients.…”
mentioning
confidence: 98%